Scientific-tecnical advances in the clasificación of periodontal diseases AND their social approach - Nivia Gontan Quintana; Carla María García San Juan (Medisur)
The development of science and technology imposes a revision of concepts that must be adjusted to the evidence that arises from the advances of science itself. Within the particular sciences, reference can be made to the field of Stomatology, whose development has generated subspecialties such as Periodontics. For many years, classification systems for periodontal diseases have been proposed and designed, which have made it possible to increase the quality of care for patients. It is the duty of every health professional to provide the best possible care and make it available and accessible to all of society. The aim of this research is to analyze, from a science-technology and society approach, the evolution of the classifications of periodontal disease from an appropriate perspective to the social reality in which both the professional and the patient develop, in order to achieve a positive impact that results in the population’s quality of life increase. A bibliographic review was carried out that was characterized by the selection of studies and the search strategy. The keywords: science, technology, society, periodontics, classification were used. The information sources consulted were Google Scholar; PubMed; Cochcrane; MediSur. 20 articles were selected. It was concluded that in periodontics it is necessary to update knowledge taking into account scientific-technical advances and use them from the professionalism and ethics perspective, always for the society benefit.